Building Student Tolerance Through A Seminar On Religious Moderation At Mts A. Yani Wonotunggal - Imam Hafid Al Ghozali; Arsan Shanie; Ali Topan; Siti Khoeriyah; Eva Amalyah; Zulfa Shoviana Havidz (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This community service activity at MTs A. Yani Wonotunggal was specifically designed to enhance students' understanding of religious moderation and the importance of tolerance among various religious groups. Recognizing the growing need to develop inclusive and harmonious attitudes, the seminar aimed to build a foundation for social harmony within the school community and more than that. Attended by 60 students, the event featured interactive face-to-face sessions led by Ustadz Yasir, who delivered the materials about religious moderation, its principles, and its application in everyday life. Through these discussions, students were able to gain the key role of respecting religious differences and learned practical ways to apply moderation in their daily activities. The seminar's impact was evident, as students demonstrated an increased awareness of the need for harmony and tolerance. This activity not only deepened their understanding of religious moderation but also contributed significantly to the creation of a more peaceful, respectful, and inclusive environment within the school, fostering long-term positive relationships.